A compact multiband dielectric resonator antenna for wireless communications. Issue 9 (25th April 2020) - Guo, Qianqian; Zhang, Jingwei; Zhu, Jiajia; Yan, Dandan
Abstract: A compact multiband rectangular dielectric resonator antenna (RDRA) is proposed in this study for worldwide interoperability for microwave access, wireless local area network, and fifth‐generation applications. The dielectric resonator antenna is fed by a 2‐slot etched coplanar waveguide with a conformal strip feed, a dielectric resonator with a dielectric constant of 37 is used and embedded into the substrate, and a foam substrate is used as a holder. The RDRA exhibits multiband and omnidirectional radiation patterns by generating a monopole mode as well as the typical TE δ 11 x and TE δ 31 x modes, which provides impedance bandwidths (| S 11 | < −10 dB) of 29.0% at the first band, 15.1% at the second band, and 6.2% at the third band. Additionally, the RDRA achieves a maximum total efficiency of 94.4% at 4.8 GHz and an overall total efficiency of 70% at the desired frequency bands.